A Study on an Extrapolation Method for the Propulsive Performance of the Pumpjet Propulsor of a Submarine - Woo-Seok Jin; Moon-Chan Kim; Jin-Wook Kim; Il-Ryong Park; Han-Shin Seol (Journal of Marine Science and Engineering, 2026)
Accurately predicting the full-scale performance of submarines is challenging due to their complex propulsor systems and limited sea-trial information. This study investigated a full-scale extrapolation method from model tests for a submarine pumpjet propulsor, as a reliable method has not been established. Three extrapolation methods from ITTC reports were reviewed and applied to the pumpjet propulsor of the SUBOFF submarine, then compared with full-scale CFD results. Among the reviewed methods (Methods 1 to 3), Method 3, which separates the duct and stator as appendages of the hull and includes the entire pumpjet in the POW test but uses only the rotor’s force, was the most reasonable, but showed significant differences from the calculated results, especially in the PD. This study proposed a modified Method 3, improving it by adopting the continuity theory to predict the oncoming velocity of a rotor and by applying a correction factor for the drag of the duct and stator. The modified PJP extrapolation method 3 showed excellent agreement with the full-scale CFD analysis results across all propulsion coefficients, with a minimal error of 0.45% for PD. Despite the structural differences in PJPs, such as stators and longer ducts, velocity changes are dominated by the duct’s internal area. Therefore, the proposed extrapolation method is equally applicable to general ducted propellers.